2015
DOI: 10.1007/s10551-015-2694-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture, Moral Disengagement, and Accident Underreporting

Abstract: Moral disengagement (MD) is the process by which individuals mitigate the consequences of their own violations of moral standards. Although MD is understood to be co-determined by culture norms, no study has yet explored the extent to which MD applied to safety at work (JS-MD) fosters safety violations (e.g., accident underreporting), nor the role of organizational culture as a predictor of JS-MD. The current study seeks to address this gap in the literature by examining individual-(MD) and organizational-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…According to the social cognitive theory of moral disengagement, individuals exert cognitive control over their feelings, thoughts, and behaviors based on their own internal and external moral standards about how one should behave (Bandura et al, 1996). Moreover, moral disengagement is not an invariable individual cognitive mechanism; it can be shaped by situational factors (Fida et al, 2015;Petitta et al, 2017), and moral self-regulation processes can be deactivated by a series of cognitive mechanisms elicited by specific environmental demands to behave in ways that conflict with ethical values (Bandura, 1991;Moore, 2008). It specifies eight mechanisms of moral disengagement that are grouped into three sets (Bandura, 1999) that facilitate the justification of deviant or unethical behaviors (Beu and Buckley, 2004;Zhang P. et al, 2018).…”
Section: Authoritarian-benevolent Leadership and Moral Disengagementmentioning
confidence: 99%
“…According to the social cognitive theory of moral disengagement, individuals exert cognitive control over their feelings, thoughts, and behaviors based on their own internal and external moral standards about how one should behave (Bandura et al, 1996). Moreover, moral disengagement is not an invariable individual cognitive mechanism; it can be shaped by situational factors (Fida et al, 2015;Petitta et al, 2017), and moral self-regulation processes can be deactivated by a series of cognitive mechanisms elicited by specific environmental demands to behave in ways that conflict with ethical values (Bandura, 1991;Moore, 2008). It specifies eight mechanisms of moral disengagement that are grouped into three sets (Bandura, 1999) that facilitate the justification of deviant or unethical behaviors (Beu and Buckley, 2004;Zhang P. et al, 2018).…”
Section: Authoritarian-benevolent Leadership and Moral Disengagementmentioning
confidence: 99%
“…Based on moral disengagement theory, this research aims to explain why consumer 'behave unethically knowingly'. Different from prior studies adopting The Theory of Planned Behaviour in the literature of consumer ethics, we found that moral disengagement theory contributes to explaining this 'attitude-behaviour' gap due to its flexible and realistic assumptions [13]. As a result, this study adopts group norms and the self-interest as the precursors of the unethical consumer behavioural intention; it explores the mediating role of moral disengagement based on moral disengagement theory and the moderating role of moral identity.…”
Section: Introductionmentioning
confidence: 66%
“…Although moral disengagement is an intrinsic psychosocial mechanism, it can be influenced by other situational factors. Prior studies have indicated that the effect moral disengagement has depends on the interaction between individuals' characteristics and the environmental variables [13]. According to social-cognitive theory, an individual's cognition dynamically adjusts with changes in the external environment, and the rationality of self-behaviour is based on moral standards and perceived environmental factors.…”
Section: The Mediating Role Of Moral Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Fear is the first feeling experienced after having an accident with biological material, and it is enhanced by the possibility of judgment and reprehension by their peers and managers. 18 When compared to the conducts recommended by the Brazilian management bodies, such as the Ministry of Health and the National Health Surveillance Agency, 15 in case of an accident with biological material, the actions performed by the victims were often inadequate. Proper care includes local care in the affected region, reporting and follow-up.…”
Section: 12mentioning
confidence: 99%